Studi Eksprimental Dengan Metode Marshall Pemanfaatan Plastik Polystyrene Sebagai Bahan Aspal AC-BC - Adnan Adnan; Mirsandy Mirsandy; Hamka Hamka (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Polystyrene plastic waste is difficult to decompose naturally and becomes microplastics which pollute the environment. Therefore, plastic waste is utilized in road pavement mixtures. This research aims to find out whether the addition of Polystyrene to AC-BC asphalt with levels of 4% and 5% can improve the quality of asphalt based on the 2018 General Bina Marga specifications. This research was carried out in a laboratory and analyzed using the Marshall method. AC-BC asphalt test results with polystyrene content of 4% and 5%, show that only the VIM value at 4% plastic content with a value of 3.88% meets and 5% plastic content with a value of 2.58% does not meet the range of 3%-5%. , then apart from the VIM value of AC-BC asphalt it meets the specifications. Keywords: AC-WC, AC-BC, Polystyrene, Marshall